Some Glaciers of the Stauning Alper, Northeast Greenland. - Pert, G. J. (Meddelelser om Grønland, 1971)
A Study of the glaciers of lhe northern Stauning Alper is presented. The moraine structure of the glaciers is discussed with reference to the recent glacial recession in the area. A mass balance of the lower regions of a typical glacier is presented and shows a considerable deficit at the snout. The overall picture of glacier recession in the region is compared with that shown by neighboring parts of the North Atlantic Coast line, and shows very similar effects.